Interpreting Duns Scotus critical essays - Pini, Giorgio 1968- (Cambridge University Press, 2022)
John Duns Scotus is commonly recognized as one of the most original thinkers of medieval philosophy. His influence on subsequent philosophers and theologians is enormous and extends well beyond the limits of the Middle Ages. His thought, however, might be intimidating for the non-initiated, because of the sheer number of topics he touched on and the difficulty of his style. The eleven essays collected here, especially written for this volume by some of the leading scholars in the field, take the reader through various topics, including Duns Scotus's intellectual environment, his argument for the existence of God, and his conceptions of modality, order, causality, freedom, and human nature. This volume provides a reliable point of entrance to the thought of Duns Scotus while giving a snapshot of some of the best research that is now being done on this difficult but intellectually rewarding thinker